2015
DOI: 10.1590/0104-1169.0489.2639
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care Evaluation: the view of clients and professionals about the Family Health Strategy

Abstract: Objective: to evaluate the attributes of primary health care as for access; longitudinality; comprehensiveness; coordination; family counseling and community counseling in the Family Health Strategy, triangulating and comparing the views of stakeholders involved in the care process. Method: evaluative research with a quantitative approach and cross-sectional design. Data collected using the Primary Care Assessment Tool for interviews with 527 adult clients, 34 health professionals, and 330 parents of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1
23

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 12 publications
6
27
1
23
Order By: Relevance
“…However, another study has shown that, even among women, the demand for nurses is very low (5.5%), demonstrating the non-recognition by the population of the identity of the professional wearing white in the health units, due to lack of presentation during the nursing consultation or by the non-development of actions that guarantee visibility to the nurse (19) . As far as referral for care being the urgency of a public hospital or private clinic, the data were higher than those of another study, which found that 10.07% of the adult users surveyed felt connected to the hospital, emergency room or emergency room service (11) . In this sense, when analyzing the difficulties of access of men to PHC in Macaíba, Rio Grande do Norte (Brazil), a study identified that 84% preferred hospitals and emergency rooms, 8% sought pharmacies and another 8%, medical clinics (20) .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…However, another study has shown that, even among women, the demand for nurses is very low (5.5%), demonstrating the non-recognition by the population of the identity of the professional wearing white in the health units, due to lack of presentation during the nursing consultation or by the non-development of actions that guarantee visibility to the nurse (19) . As far as referral for care being the urgency of a public hospital or private clinic, the data were higher than those of another study, which found that 10.07% of the adult users surveyed felt connected to the hospital, emergency room or emergency room service (11) . In this sense, when analyzing the difficulties of access of men to PHC in Macaíba, Rio Grande do Norte (Brazil), a study identified that 84% preferred hospitals and emergency rooms, 8% sought pharmacies and another 8%, medical clinics (20) .…”
Section: Discussioncontrasting
confidence: 59%
“…The value of the scores (E) was standardized for a scale ranging from 0 to 10, done by applying the score in the formula: E = [(score-1) × 10] / 3 (10) . Services with a quality score of 6.6 or higher were considered strongly oriented to the quality of PHC, while values lower than 6.6 were considered low quality (11) . The degree of affiliation to the health service / health professional, that is, how much the user recognizes the service or the health professional as a reference for health care, corresponds to the first part of PCA Tool and was calculated using the scoring algorithm from 1 to 4 (9) .…”
Section: Study Protocolmentioning
confidence: 99%
“…This is in line with research that identified little knowledge of the history of health and living conditions of the customers and families by FHS professionals. (13) Such situations implicate in the recovery their meaning for healthcare practice, in order to establish planning that is coherent with the social, economic and health reality.…”
Section: Discussionmentioning
confidence: 99%
“…(25) These findings are in agreement with other studies with a context of children's health. (19,14,(20)(21)(22) Although the Derivative and Essential Elements scores did not attain satisfactory values, the specialized services presented better results than the PHC services, showing that, from the perception of the consumers significant differences between the services. The specialized services were perceived as regular sources of care, and better providers of health practices, based on the attributes of PHC.…”
Section: Discussionmentioning
confidence: 91%
“…(18) The attribute, Family Orientation, presupposes greater interaction between health professionals and the family, and the recognition of the potential of the family context being of extreme importance for comprehensive care.. (14) In the present investigation, this attribute attained an unsatisfactory score, indicating that health actions aimed at the family context are fragile and poorly recognized, corroborating other evaluative studies related to the child's health, which obtained similar results. (14,(19)(20)(21)(22) . Family health care with poor orientation can also lead to fragility of comprehensiveness; if the life contexts of individuals and their families are not perceived or known, the involvement and concern for extended care, with commitment to all their needs, may not be effective.…”
Section: Discussionmentioning
confidence: 99%